EXPLORATION OF SELF DISCLOUSURE : A PSYCHOSOCIAL BARRIER OF MERANTAU STUDENTS - Alfi Rahmi; Firman Firman; Yarmis Syukur; Noor Syamilah Zakaria (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
Self Disclosure is one of the social skills that must be possessed, especially for overseas students. These social skills will give birth to social interactions that will create good psychosocial conditions in social relationships. This study aims to describe the level of self-disclosure of overseas students in the Guidance and Counseling study program at the Bukittinggi State Islamic University. This type of research includes a quantitative descriptive research instrument, namely the self-disclosure scale. The population in the study were guidance and counseling students from outside West Sumatra, totaling 43 people. Sampling was taken using a non-probability sampling technique with a purposive sampling technique. The results of the study revealed that the self-disclosure level of overseas students at Bukittinggi State Islamic University was in the moderate category with 65.11% while the highest self-disclosure aspect was in the aspect of cultural perception. Research findings based on gender reveal that female students are more open than male students, namely in the aspects of perception of culture, perception of gender, perception of listeners, and perception of topics while men are more open in aspects of self-knowledge.